Can big data analytics improve the quality of decision-making in businesses? - Haque Sazu, Mesbaul (2022)
Big Data Analytics initiatives are crucial for changing conventional firms' decision-making directly into a data driven one that helps achieve the firm's goals. Nevertheless, prior information methods analysis has not given sufficient interest in the effect of Big Data Analytics use on decision-making quality. Using the computational ability of Data Analytics, this analysis examined the effect of Big Data Analytics on decision-making quality and evaluated the mediating impact of Data Analytics capabilities. We collected information through 480 software companies in America. The empirical outcomes demonstrated that big data analytics usage had a positive effect on decision-making quality, where Big Data Analytics had a mediating role in the relationship between Big Data Analytics use and decision-making quality. Thus, companies should not only popularize Big Data Analytics use in business activities, but also take steps to boost the data analytics capabilities, which will boost the decision-making quality in the direction of acquiring competitive advantage.